1999
DOI: 10.1055/s-1999-29
|View full text |Cite
|
Sign up to set email alerts
|

A New Device for Abrasive Cytology Sampling During Upper Gastrointestinal Endoscopy: Experience in Infectious and Neoplastic Diseases

Abstract: This new device provides a fast and low-cost method of isolating pathogens and obtaining cell fragments from the gastrointestinal mucosa during routine upper gastrointestinal endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Subsequent to the first report by Vilmann et al . of endoscopic ultrasonography‐guided fine‐needle aspiration (EUS‐FNA) for pancreatic tumors, 6 cytology or histology materials collected using EUS‐FNA have become widely used for diagnosis of GIST 6–12 . With this method, it has been reported that the accuracy in gastrointestinal diseases such as submucosal tumor was high (38–100%), and that complications including bleeding and infection were rare (0–2.6%), compared to conventional EUS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to the first report by Vilmann et al . of endoscopic ultrasonography‐guided fine‐needle aspiration (EUS‐FNA) for pancreatic tumors, 6 cytology or histology materials collected using EUS‐FNA have become widely used for diagnosis of GIST 6–12 . With this method, it has been reported that the accuracy in gastrointestinal diseases such as submucosal tumor was high (38–100%), and that complications including bleeding and infection were rare (0–2.6%), compared to conventional EUS.…”
mentioning
confidence: 99%
“…For histological diagnosis, mitotic count, subclassification into spindle cell, epithelioid cell, and mixed cell, and immunohistochemistry is used for diagnosis 1,3,12,15 . Only a few reports of cytological findings, however, have been published 8,11–13 . Therefore, cytological diagnostic criteria have yet to be established for routine application.…”
mentioning
confidence: 99%